2019
DOI: 10.3389/fonc.2019.00624
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib Prior to Selective Internal Radiation Therapy Using 90Y-Resin Microspheres for Refractory Metastatic Colorectal Cancer Liver Metastases: Analysis of Safety, Dosimetry, and Molecular Markers

Abstract: Background: This Phase II, open-label, study examined the safety of regorafenib followed by selective internal radiation therapy (SIRT) with regorafenib re-initiation in the treatment of metastatic colorectal cancer (mCRC) patients with liver metastases who are not surgical candidates. Methods: Patients received 160 mg regorafenib daily on a 21-day course followed by a 1 week washout prior to SIRT. Liver function was evaluated at 2 and 4 weeks after SIRT, and regorafenib re-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…The ORR advantage obtained from regorafenib combined with radiotherapy in this study also translated into a survival advantage. The patients achieved a mPFS of 7.89 months and a mOS of 16.85 months; these figures are superior to those previously reported for regorafenib combined with selective internal irradiation radiotherapy ( 27 ) (i.e., a mPFS of 3.7 months and a mOS of 12.1 months). This may be related to the patients’ baseline data; the enrolled patients in previous study had liver metastasis.…”
Section: Discussioncontrasting
confidence: 57%
“…The ORR advantage obtained from regorafenib combined with radiotherapy in this study also translated into a survival advantage. The patients achieved a mPFS of 7.89 months and a mOS of 16.85 months; these figures are superior to those previously reported for regorafenib combined with selective internal irradiation radiotherapy ( 27 ) (i.e., a mPFS of 3.7 months and a mOS of 12.1 months). This may be related to the patients’ baseline data; the enrolled patients in previous study had liver metastasis.…”
Section: Discussioncontrasting
confidence: 57%
“…The Von Willebrand Factor ( VWF ) is a marker for angiogenesis, and it has been suggested as a predictive biomarker for therapeutic response in pancreatic cancer [ 76 ]. A decrease in VWF expression is associated with improved survival in patients with colorectal cancer and liver metastases [ 77 ], and a single nucleotide polymorphism in VWF (rs73049469) is associated with overall survival in NSCLC [ 78 ]. VWF is also upregulated in androgen-independent prostate cancer cells [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 In a phase II trial, 22 patients with unresectable mCRC of the liver received 160 mg regorafenib daily for 21 days, followed by a 1-week washout prior to Y90 administration; if liver function remained normal 4 weeks after Y90, regorafenib was reinitiated. 31 Dose adjustments and delays were allowed per the discretion of the treating physicians. 68% of the cohort required dose reductions and 80% required dose interruptions.…”
Section: Molecular Agentsmentioning
confidence: 99%
“…The authors concluded that addition of regorafenib to Y90 was safe and tolerable, with a safety profile comparable to regorafenib monotherapy. 31 The molecular agent cetuximab is a potent radiosensitizer, although there are no clinical studies focused on its safety and toxicity when used in combination with Y90. As mentioned previously, bevacizumab, also frequently used in the treatment of mCRC, may not necessarily have synergistic toxic effects with Y90, but it may increase the risk of arteriography complications.…”
Section: Molecular Agentsmentioning
confidence: 99%